Special edition using Microsoft Project 2002 - Pyron, Tim (Que, 2002)
Special Edition Using Microsoft Project 2002 gives you direct answers about how to put a project schedule together with this best-selling project management software. It's organized to follow the project cycle of initializing and developing a plan, implementing the plan, tracking and analyzing progress, adjusting to changes and unforeseen events, and preparing the final reports. You'll find step-by-step procedures for using Project's features, plus you'll get help with common problems.